Pola Pendidikan Iklusif (Studi Bagi Anak Yang Mengalami Emosional Dan Perilaku) : (Studi Bagi Anak Yang Mengalami Emosional Dan Perilaku) - Ayuni, Audy; Rusmaida, Cici; Ramadhan , Habibie; Aulia Rahman, Nadila; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
The pattern of inclusive education represents the provision of educational opportunities for students with disabilities and special intellectual or talented abilities, allowing them to participate in learning within an inclusive educational environment. Students with special needs, such as those experiencing complex emotional development, hyperactivity, and poor concentration, often encounter challenges in the learning process. These disorders affect their ability to control emotions, which, in turn, influences their engagement and understanding of self-concept. This research was conducted at the ABC Melati Special School to explore the aspects of emotional and behavioral development in students. Observation, interviews, and documentation methods were employed to collect descriptive data, encompassing words, descriptions, and behaviors of the students. The study aims to provide a deeper understanding of the challenges faced by students with special needs in the context of inclusive education and advocate for a more holistic educational approach.